A New Insight Into the Mechanism of the Ring‐Opening Polymerization of Trimethylene Carbonate Catalyzed by Methanesulfonic Acid. Issue 1 (19th November 2012) - Campos, João M.; Ribeiro, Maria R.; Ribeiro, Maria F.; Deffieux, Alain; Peruch, Frédéric
Abstract The ring‐opening polymerization (ROP) of trimethylene carbonate (TMC) initiated by a monoalcohol and catalyzed by CH3SO3H is investigated, in an effort to reveal extra features of the known activated monomer/active chain‐end (AM/ACE) combined mechanism. Size‐exclusion chromatography (SEC) profiles obtained with high‐molar‐mass samples show a poly(trimethylene carbonate) (PTMC) fraction generated by AM/ACE with a molar mass that is exactly twice that of the PTMC fraction coming from pure AM. Conversely, PTMC prepared with a diol is perfectly unimodal and keeps its molar mass dispersity below 1.1. This suggests that the side AM/ACE mechanism may be a bidirectional AM mechanism, and that PTMC with a narrow unimodal molar‐mass distribution can be obtained easily from a diol regardless of this side propagation.